Saliva: A potential media for disease diagnostics and monitoring - Liu, Jingyi; Duan, Yixiang (Oral oncology, 2012)
Within the past 10years, the use of saliva as a diagnostic tool has gained considerable attention and become a well-accepted method. As a diagnostic fluid, saliva offers superiority over serum due to both a noninvasive collection method by specially trained persons and a cost-effective approach for screening of large populations. Collection of saliva offers a reduced risk of infection compared to the collection of serum. Moreover, obtaining saliva samples from infant, disabled or anxious patients, is much easier than obtaining other samples. There is a lot of useful components-changing information in saliva when a person is in sick. Therefore, we define these changing components as “biomarkers”. The utilization of biomarkers as early predictors for clinical disease not only contributes to the effective prevention and treatment of diseases, but also enhances the assessment of potential health risks. In this article, we have reviewed the properties of saliva, the salivary analysis method for biomarker discovery, and the diagnostic potentials of salivary biomarkers in monitoring and detecting periodontal disease, Oral and Breast cancers, and Sjögren’s syndrome. We also discussed some barriers of applications of saliva as a diagnostic media as well as recent improvements. We also prospected the future processing directions of using biomarkers in disease diagnosis and draw a conclusion that saliva is indeed an effective media in various disease monitoring and diagnosis.